Elicitation of particular grammatical structures in speeches for interpreting research: enhancing ecological validity of experimental research in interpreting. (4th July 2021) - Baekelandt, Annelies; Defrancq, Bart
ABSTRACT: In many experiments with simultaneous interpreting (SI), researchers use source speeches that are not only written and read aloud, but also pre-recorded, reducing their ecological validity. This study proposes a method to obtain speeches that are suited for experimental research, but with lower levels of input control. It examines the effect of written cues in a PowerPoint presentation with varying constituent orders and varying ratios of explicit verbal input. The study analyses to what extent the cues are capable of eliciting SOV (subject – object – verb) constituent orders in Dutch speakers, a well-known trigger of cognitive load in SI. We focus on two types of subordinate clauses: adverbial and content clauses. The results reveal that the extent to which SOV is elicited in speakers is highest when the (S)OV order is present in the written input. However, other types of input, with lower levels of input control, such as verbless structures, are also seen to elicit to 50% of SOV in speeches.